2001
DOI: 10.1130/1052-5173(2001)011<0004:ehgatg>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Erosion, Himalayan Geodynamics, and the Geomorphology of Metamorphism

Abstract: Is erosion important to the structural and petrological evolution of mountain belts? The nature of active metamorphic massifs colocated with deep gorges in the syntaxes at each end of the Himalayan range, together with the magnitude of erosional fluxes that occur in these regions, leads us to concur with suggestions that erosion plays an integral role in collisional dynamics. At multiple scales, erosion exerts an influence on a par with such fundamental phenomena as crustal thickening and extensional collapse.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
296
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 456 publications
(310 citation statements)
references
References 42 publications
12
296
0
2
Order By: Relevance
“…Such a perspective is therefore still far from clear promoting us to pursue further studies of the molecular phylogenetics of the sisorid catfishes. It has long been recognized that paleo-drainages of major continental East Asian Rivers, draining the south-eastern Tibet plateau margin, differed markedly from their current drainage patterns (Brookfield, 1998;Clark et al, 2004;Gregory, 1925;Gregory and Gregory, 1923;Hallet and Molnar, 2001;Métivier et al, 1999;Seeber and Gornitz, 1983;Zeitler et al, 2001). In a recent study, Clark et al (2004) suggested that these rivers were once tributaries to a single southward flowing system, which drained into the South China Sea (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Such a perspective is therefore still far from clear promoting us to pursue further studies of the molecular phylogenetics of the sisorid catfishes. It has long been recognized that paleo-drainages of major continental East Asian Rivers, draining the south-eastern Tibet plateau margin, differed markedly from their current drainage patterns (Brookfield, 1998;Clark et al, 2004;Gregory, 1925;Gregory and Gregory, 1923;Hallet and Molnar, 2001;Métivier et al, 1999;Seeber and Gornitz, 1983;Zeitler et al, 2001). In a recent study, Clark et al (2004) suggested that these rivers were once tributaries to a single southward flowing system, which drained into the South China Sea (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The eastern syntaxis of the Himalaya, which marks the eastern edge of the collision between the Indian and Eurasian plates, is characterized by particularly high rates of exhumation and erosion. Here rock uplift rates are some of the highest in the world (up to 10 mm/yr; Burg et al, 1998) and are in part driven by rapid river incision of the Brahmaputra and glacial removal of bedrock (Zeitler et al, 2001). These rapid rates of erosion are evidenced by a steep river profile, high erosive index, and elevated stream power (Finlayson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the extent of glaciers and snow cover on the Tibetan Plateau provide significant feedbacks in climate modelling, which requires understanding the nature of glacial fluctuations (Dey and Bhanu Kumar, 1982;Dey et al, 1985;Bush, 2000). Tibet is also an ideal natural laboratory to examine the relationship between global climate and the processes of continental-continental collisions, tectonic aneurysm (Zeitler et al, 2001) and glacial buzzsaw (Porter, 1989;Brozovic et al, 1997) models.…”
Section: Introductionmentioning
confidence: 99%